2020
DOI: 10.1159/000507370
|View full text |Cite
|
Sign up to set email alerts
|

A Changing Paradigm for the Treatment of Intermediate-Stage Hepatocellular Carcinoma: Asia-Pacific Primary Liver Cancer Expert Consensus Statements

Abstract: The Asia-Pacific Primary Liver Cancer Expert (APPLE) Consensus Statement on the treatment strategy for patients with intermediate-stage hepatocellular carcinoma (HCC) was estab

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 211 publications
(260 citation statements)
references
References 91 publications
(122 reference statements)
5
235
0
Order By: Relevance
“…18,21,38 In the 10th Asia-Pacific Primary Liver Cancer Expert Meeting (APPLE 2019), CMN type and poorly differentiated HCCs were defined as "unlikely to respond to TACE". 39 Katayama et al reported that CMN type showed significantly higher recurrence after TACE. 40 In our study, CMN type showed poor prognosis in the univariate analysis but not in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…18,21,38 In the 10th Asia-Pacific Primary Liver Cancer Expert Meeting (APPLE 2019), CMN type and poorly differentiated HCCs were defined as "unlikely to respond to TACE". 39 Katayama et al reported that CMN type showed significantly higher recurrence after TACE. 40 In our study, CMN type showed poor prognosis in the univariate analysis but not in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…New paradigm of treatment strategy in HCC The concept of TACE-unsuitable HCC has also been gaining attention in recent years [47,48]. This covers 3 patient types: (1) patients prone to becoming refractory to TACE, (2) patients whose hepatic functional reserve is likely to drop to Child-Pugh B on TACE, and (3) patients basically resistant to TACE [49]. Patients who do not meet the up-to-seven criteria would fall under the first 2 categories [49].…”
Section: Keynote-240mentioning
confidence: 99%
“…This covers 3 patient types: (1) patients prone to becoming refractory to TACE, (2) patients whose hepatic functional reserve is likely to drop to Child-Pugh B on TACE, and (3) patients basically resistant to TACE [49]. Patients who do not meet the up-to-seven criteria would fall under the first 2 categories [49]. The use of lenvatinib as the initial treatment produces 3 main effects in such patients: it (1) downstages the tumor by inducing necrosis, (2) inhibits progression and metastasis by decreasing the release of VEGF, and (3) increases the effectiveness of TACE by improving the delivery of Lipiodol mixed with anticancer drugs due to normalization of the tumor vasculature.…”
Section: Keynote-240mentioning
confidence: 99%
“…• Use prognostic factors such as up-to-seven criteria and ALBI grade to select appropriate patients for TACE (up-to-seven in) and systemic therapy (up-to-seven criteria out, mALBI grade 2b) 7,31,[33][34][35] • Consider alternative treatment, such as systemic therapy (preferably lenvatinib) for TACE-unsuitable patients (simple nodular type with extranodular growth type, confluent multinodular type, poorly differentiated type, etc. ), based on macroscopic tumor classification and differentiation 31,[35][36][37][38] Alternative therapy: systemic therapy (lenvatinib, etc.) Systemic therapy…”
Section: General Mattersmentioning
confidence: 99%
“…49 Systemic therapy should be considered for patients not indicated for TACE, including those classified as up-to-seven criteria OUT patients or patients with ALBI grade 2 (particularly mALBI grade 2b). [33][34][35][50][51][52][53][54] Systemic therapy should also be considered when TACE is not indicated based on macroscopic classification and degree of differentiation, which include tumors beyond simple nodular type with extranodular growth, confluent multinodular type or poorly differentiated type. [35][36][37]55 Avoiding or postponing hospital admission and replacing TACE with systemic therapy, preferably using agents with high response rates such as lenvatinib, should be considered.…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%